Effect of Bran Media Variation on Maggot Growth in Waste Management - Mawan Eko Defriatno; Siti Muyasaroh; Wahyu Nur Achmadin (Universitas Panca Marga, 2025)
This study aims to evaluate the effect of bran variation on the growth of black soldier fly larvae (Hermetia illucens) under controlled initial conditions of 250 g larvae and 250 g organic waste. The experiment was conducted using different doses of bran supplementation (20–200 g), with daily observations of larval weight changes over 11 days. The results indicate that bran addition significantly influenced larval growth rate. Moderate doses (60–100 g) produced higher and more consistent weight gain compared to low doses (20–40 g) or excessive doses (160–200 g). The highest growth was observed in the 80 g treatment, reaching 890 g on day 10 before declining on day 11. In conclusion, moderate bran supplementation provides the most optimal medium conditions for larval growth, while insufficient or excessive amounts tend to be less efficient.